2022
DOI: 10.3390/gels8120791
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Poly(vinyl alcohol)–tetraethylorthosilicate Hybrid Gel Electrolyte for Lead Storage Battery

Abstract: The gel electrolyte significantly influences gel valve-regulated lead acid battery performance. To address this, the paper describes the preparation of novel polymer gel electrolytes using poly (vinyl alcohol) (PVA) and tetraethylorthosilicate (TEOS) for valve-regulated lead–acid batteries. FTIR technique is used to confirm the chemical reaction between PVA and TEOS. Electrochemical analyses such as cyclic voltammetry and electrochemical impedance spectroscopy were applied to optimize the concentration of PVA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…30 Furthermore, the peaks at 1343 cm −1 and 878 cm −1 are associated with the stretching vibrations of SO and S–OH in H 2 SO 4 in the gel systems. 31,32…”
Section: Resultsmentioning
confidence: 99%
“…30 Furthermore, the peaks at 1343 cm −1 and 878 cm −1 are associated with the stretching vibrations of SO and S–OH in H 2 SO 4 in the gel systems. 31,32…”
Section: Resultsmentioning
confidence: 99%
“…At 1625 cm –1 , the CO carbonyl stretching vibration’s peak may be noticed. Further multiple bands that appeared in the spectra at 1166 and 1041 cm –1 were assigned to CO stretching vibrations. , With the addition of graphene in the PVA matrix, bands corresponding to the OH stretching vibration and CO stretching vibration shift to a higher wavenumber marginally. These results suggest that there exists trace hydrogen bonding between the PVA and graphene .…”
Section: Resultsmentioning
confidence: 99%
“…44 Furthermore, the peaks at 1333 and 878 cm −1 are associated with the stretching vibrations of S�O and S�OH in H 2 SO 4 in GPEs. 45 Ionic Conductivity Study. Ionic conductivity is the fundamental criterion for GPE and depends on mobile ions present in GPE.…”
Section: ■ Experimentsmentioning
confidence: 99%
“…[ 59 ] However, the peaks at 1338 and 874 cm −1 are associated with the stretching vibrations of S=O and S−OH in H 2 SO 4 in GPEs. [ 60 ] As the content of HNC increases, the intensity of these peaks gradually decreases. This may be attributed to the adsorption of sulfuric acid molecules onto the HNC surface.…”
Section: Resultsmentioning
confidence: 99%
“…The anodic potential at −0.43 V suggests the conversion of Pb to PbSO 4 and the cathodic potential at −0.38 V suggests the conversion of PbSO 4 to Pb which are the electrode reactions taking place in a lead acid battery. [ 63 ] Peak currents of 0.024, 0.026, 0.033, 0.086, and 0.057 A were recorded for G‐0, G‐1, G‐2, G‐3, and G‐4 respectively. From Figure 2h, it was observed that the highest anodic peak current was obtained for G‐3.…”
Section: Resultsmentioning
confidence: 99%